Power electronics handbook : components, circuits, and applications - Mazda, F. F. (Butterworth, 1990)
Power Electronics Handbook: Components, Circuits, and Applications is a collection of materials about power components, circuit design, and applications. Presented in a practical form, theoretical information is given as formulae. The book is divided into three parts. Part 1 deals with the usual components found in power electronics such as semiconductor devices and power semiconductor control components, their electronic compatibility, and protection. Part 2 tackles parts and principles related to circuits such as switches; link frequency chargers; converters; and AC line control, and Part 3.